Implementasi Openstack untuk Private Cloud pada mata kuliah Administrasi server - Roberto Firman; Yuhefizar; Hidra Amnur (SOTVI - Society of Visual Informatics, 2020)
In Server Administration learning requires a comprehensive infrastructure and specifications along with increasing server needs. By overcoming the constraints of infrastructure constraints, Cloud Computing offers a more efficient and flexible server infrastructure. One of the platforms that offers infrastructure and server specifications is Openstack. Cloud computing technology is built using the Ubuntu Server 18.04 operating system and the Victorian version of the OpenStack deploying platform with Devstack. The results of this final project are implemented and used in network laboratories. Openstack can run 30 users. The creation of instances based on flavors of sizes m1.nano, m1.micro, cirros256, m1.tiny, ds512m, ds1G and m1.small. The images used on the instances are cirros-0.5.1-x86_65-disk and Ubuntu Server 18.04.